2019
DOI: 10.3390/v11020135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pullet Vaccination on Development and Longevity of Immunity

Abstract: Avian respiratory disease causes significant economic losses in commercial poultry. Because of the need to protect long-lived poultry against respiratory tract pathogens from an early age, vaccination programs for pullets typically involve serial administration of a variety of vaccines, including infectious bronchitis virus (IBV), Newcastle disease virus (NDV), and infectious laryngotracheitis virus (ILTV). Often the interval between vaccinations is only a matter of weeks, yet it is unknown whether the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The exemplary studies were performed for vaccine against infectious bronchitis virus (60). In addition, the effect of interval between vaccinations against different viral pathogens on protection against challenge has been extensively tested [e.g., (61)]. Such studies result in recommended vaccination programs for individual poultry sectors, as presented in the Merck Veterinary Manual (62).…”
Section: Discussionmentioning
confidence: 99%
“…The exemplary studies were performed for vaccine against infectious bronchitis virus (60). In addition, the effect of interval between vaccinations against different viral pathogens on protection against challenge has been extensively tested [e.g., (61)]. Such studies result in recommended vaccination programs for individual poultry sectors, as presented in the Merck Veterinary Manual (62).…”
Section: Discussionmentioning
confidence: 99%
“…These vaccines elicit the immune response by causing infection in the trachea without producing disease. The highest protective immunity is attained from 15 to 20 weeks post-vaccination, which may last over a year (Neff et al 2008) and no interference has been reported between ILT and other vaccines if the vaccine interval is more than 2 weeks (Aston et al 2019). ILTV vaccination is not suggested for broilers because of its economical concern (Giambrone et al 2008).…”
Section: Vaccinationmentioning
confidence: 99%
“…Instead, production of neutralizing antibodies is relatively low and curiously short‐lived after human infection with the common cold coronavirus HCoV‐229E 22,23 or after clinically severe infections with SARS‐CoV 24,25 . Short‐lived antibody formation also limits the utility of live attenuated vaccines against infectious bronchitis coronavirus in the poultry industry 26,27 . Whereas influenza escapes our mechanisms for neutralizing antibody production by high viral genome mutation rates, coronaviruses avoid the fitness cost of high mutation rates by somehow manipulating our mechanisms for neutralizing antibody responses so that they are low titer, short lived and do not stop virus transmission in the population 23 …”
Section: Genetic Resistance To Virus Transmissionmentioning
confidence: 99%